Aluminum toxicity reduces the nutritional efficiency of macronutrients and micronutrients in sugarcane seedlings - Borges, Carolina Eggers [UNESP]; Cazetta, Jairo Osvaldo [UNESP]; de Sousa, Francisco Bruno Ferreira [UNESP]; Oliveira, Kamilla Silva [UNESP] (FapUNIFESP (SciELO), 2020)
Although the effects of aluminum on the content and accumulation of mineral nutrients in crops have been studied, but nothing is known about its effect on the nutritional efficiency of sugarcane. Therefore, this study aimed to evaluate the effect of aluminum toxicity on nutritional efficiency, nutrient accumulation, and growth of sugarcane seedling. Sugarcane seedlings of the genotype IACSP95-5000, obtained from one-bud mini-cuttings (3 cm), were used in the test. Seedlings were subjected to treatments in a completely randomized design, with eight Al concentrations in the nutrient solution (0, 10, 20, 30, 40, 50, 60, and 70 mg L−1) and three replicates, totaling 24 experimental units. Analyses determined the contents, accumulation, and absorption, transport, and use efficiency of macronutrients, micronutrients, and aluminum, in addition to dry matter production. The results show that Al affected all variables analyzed, with a decrease in the nutritional efficiency of macronutrients and micronutrients and a drastic decrease in the accumulation of macronutrients in the aerial part, which reflected in the decrease in the dry matter of the plants. The root system was the most affected, with a decrease in growth of up to 60%. Aluminum reduced the use efficiency of nutrient in decreasing order: Ca (69%)> N (60%)> K (59%)> Mg (50%)> S (49%)> P (40%). As for micronutrients, the following decreasing order was observed: Fe (73%)> Zn (59%) = Cu (59%)> Mn (25%).
Toxidez de alumínio reduz eficiência nutricional de macronutrientes e micronutrientes em mudas de cana-de-açúcar
Keywords: Abiotic stress; Accumulation; Acidity; Saccharum spp; Use efficiency